Escalating Antibiotic Resistance in Uremia Patients Demands Urgent Global Action: Meningkatnya Resistensi Antibiotik pada Pasien Uremia Menuntut Tindakan Global yang Mendesak - Ahmad Shandookh Hameed (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Uremia, a frequent complication of Chronic Kidney Disease (CKD), compromises immunity, increasing patients' susceptibility to bacterial infections. Multi-drug resistance (MDR) and extensively drug resistance (XDR) further exacerbate infection management challenges, particularly in regions with limited resources. Knowledge Gap: While bacterial resistance is well-documented globally, the prevalence and specific resistance patterns in uremia patients in Nasiriyah City remain underexplored. Aims: This study aimed to establish the prevalence and resistance profiles of MDR and XDR bacterial isolates among uremia patients in Nasiriyah City, with a focus on treatment implications and infection control strategies. Methods: A cross-sectional study was conducted at Al-Hussein Teaching Hospital from February 2023 to January 2024. One hundred samples from uremia patients were cultured and tested using the Kirby-Bauer disk diffusion method following CLSI guidelines. Results: The most frequently isolated bacteria were Escherichia coli (40%), Klebsiella pneumoniae (30%), Staphylococcus aureus (20%), and Pseudomonas aeruginosa (10%). High resistance rates were observed for Ampicillin (95%), Amoxicillin-Clavulanate (80%), and Ceftriaxone (75%), while resistance to Imipenem and Meropenem was lowest at 5% and 10%, respectively. Significant resistance patterns were noted across all tested antibiotics (P<0.05). Novelty: This study provides the first comprehensive analysis of MDR and XDR bacterial prevalence in uremia patients in Nasiriyah City, highlighting the critical need for targeted antibiotic stewardship. Implications: The findings underscore the urgency of implementing stringent infection control measures and developing alternative therapeutic strategies to combat the rising threat of antibiotic resistance in this vulnerable population. The efficacy of carbapenems, though still relatively preserved, necessitates cautious use to prevent further resistance development. Highlights: High resistance to common antibiotics in E. coli and K. pneumoniae. Carbapenems remain effective, with low resistance rates. Urgent need for antibiotic stewardship and alternative treatments. Keywords: Uremia, Multi-drug resistance, Antibiotic susceptibility, Nasiriyah City, Infection control